(untitled) (Research, Society and Development, 2021)
Objective: To evaluate the profile of victims traumatic brain injury (TBI) in an emergency hospital in the state of Sergipe. Methods: This is a longitudinal, observational, prospective study, with a quantitative approach to TBI victims who were admitted to the critical axis of a hospital in the state of Sergipe, in the city of Aracaju. A self-made instrument was used, based on the Domingues instrument (2013), which contains objective questions with sociodemographic and physiological data, referring to the topography and clinical information of the study. Results: From the sample of 192 patients, an average age of 36.6 years was seen, with 87.5% male and 12.5% ​​female, where 74% suffered a transport accident, the minority of a blunt mechanism. (96.4%) of the victims received pre-hospital care, with (59.9%) being discharged as an outcome while 34.4% died, patients had a median hospital stay of 11 days, with (54, 2%) of them without the need for ICU admission, the minority of them had an outcome without sequelae. Conclusion: TBI is still the main cause of transport accidents, with a prevalence of blunt trauma, where the general profile of the victims was predominantly male patients, young adults aged between 18 and 29 years. Even with the majority of patients receiving prehospital care, death rates, although lower, are still very close to discharge rates.